1996
DOI: 10.2176/nmc.36.709
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Normal Brain Tissue of Patients with Intracranial Tumors

Abstract: Pre- and postoperative cerebral blood flow (CBF) changes in the normal brain tissue of 17 patients with intracranial tumors were studied to determine the value for planning therapeutic strategy. The tumors included eight astrocytomas, seven meningiomas, one metastasis, and one arachnoid cyst. The patients were divided into two groups based on the mass effect seen on computed tomography (CT) scans. Group A comprised six patients with midline shift or evidence of herniation; Group B, 11 patients with no mass eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Growing intracranial neoplasm exhibits various effects on the peritumoral brain, such as accumulation of the edematous fluid, hypoperfusion with or without ischemia, local inflammation and diffusion of the metabolically active substances secreted by the lesion itself [1][2][3]. Any of these, in association or separately, may contribute to neuronal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Growing intracranial neoplasm exhibits various effects on the peritumoral brain, such as accumulation of the edematous fluid, hypoperfusion with or without ischemia, local inflammation and diffusion of the metabolically active substances secreted by the lesion itself [1][2][3]. Any of these, in association or separately, may contribute to neuronal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive growth and prominent peritumoral edema are more frequently observed in larger tumors with greater compressive effect on the adjacent cerebral structures [18][19][20]. Peritumoral alterations of the cerebral blood flow with or without ischemia caused by mass-effect of the neoplasm and accumulation of the edematous fluid are not uncommon in cases of intracranial meningiomas [21][22][23][24][25]. All these pathophysiological and associated histopathological abnormalities, which are presented in the "transitory zone" between the tumor border and normal brain, can be reflected in changes of 1 H-MRS-detected metabolite content.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that failure to attain statistical significance was due to the limited number of task repetitions and variability in tracer uptake and not to abolition of the blood flow response because of destruction or compression of the cortex by the mass lesion. 15 Hence we examined the correlation between the value of the t statistic peak and the results of ICS and determined t-statistic ranges that predicted the results of ICS more accurately than the simple presence or absence of statistically significant activation. We found that when there is absent or weak PET activation (t Ͻ 3.2), ICS is invariably negative and unnecessary.…”
Section: Methodological Issuesmentioning
confidence: 99%